WITHDRAWN: Using a combination of conservative and enucleating treatment to treat a large dentigerous cyst - Fahad Khan; Brian Castling (Elsevier, 2022)
The Publisher regrets that this article is an accidental duplication of an article that has already been published in Advances in Oral and Maxillofacial Surgery, Volume 8, October-December 2022, 100344, https://doi.org/10.1016/j.adoms.2022.100344 The duplicate article has therefore been withdrawn.The full Elsevier Policy on Article Withdrawal can be found at https://www.elsevier.com/about/our-business/policies/article-withdrawal.